PEMODELAN GEOLOGI DAN ESTIMASI SUMBER DAYA BATUBARA DI WILAYAH ‘X’. KABUPATEN BERAU, PROVINSI KALIMANTAN TIMUR: GEOLOGICAL MODELING AND ESTIMATION OF COAL RESOURCES IN AREA 'X', BERAU REGENCY, EAST KALIMANTAN PROVINCE - Manurung, Jekson; Nurdrajat; Alfadli, Muhammad Kurniawan; Asmoro, Yoki Dwi (Journal of Geoscience Engineering and Energy, 2024)
General geological investigation activities and detailed exploration need to be carried out, so that it can show potential coal resources that can still be developed. The research area is in the PT. Berau Coal concession area, administratively located in Berau Regency, East Kalimantan Province. The research method used in calculating resources in Region 'X' is the Polygon Method, namely by halving the distance between two sample points on one axis to produce an area of ​​influence and refers to moderate complexity based on analysis of the geological conditions of the research area (SNI 5015:2019). This research aims to determine the feasibility of a coal seam to be mined based on aspects of dimensions, quantity and quality of coal distribution, as well as a reference in design and determining appropriate mining methods based on coal geological modeling. Based on ASTM D388-19 of 2004, the research area has a High Volatile B Bituminous coal ranking with an average calorific value (dmmf) of 13111,01 Btu/lb, ash content 4,7%, total sulfur 0,98%, total moisture 21,28%, inherent moisture 16,66%, volatile matter 48,63%, and fixed carbon 51,37%. The total estimated coal resources in the research area are 14.760.000 million tons, consisting of total measured coal resources of 13.380.000 million tons, indicated 930.000 thousand tons, and inferred 410.000 thousand tons.